Clinical literature on postoperative delirium and neurocognitive disorders: a historical systematic review - Gianluca Villa; Lorenzo Foti; Tessa Piazzini; Gaetano Russo; Marin Verrengia; Corinne Sangermano; Federico Bilotta; Stefano Romagnoli (Journal of Anesthesia, Analgesia and Critical Care, 2022)
Abstract Background Since the appearance of the first report on postoperative cognitive impairment in 1955, the number of papers focusing on perioperative neurocognitive disorders (PND) has constantly increased, both in the field of basic science and clinical research. A critical comprehensive review may explore the perception of how noteworthy PND is for physicians and clinical researchers. The aim of this systematic review is to describe how the clinical papers published to date with PND as primary or secondary outcome have changed over time in terms of editorial characteristics. Results A literature search was performed on PubMed, Embase, CINAHL, Cochrane, Scopus, and Web of Science databases, up to March 2021. Human prospective or retrospective clinical studies in which incidence, risk factors, treatments, or outcomes associated with PND are described among primary or secondary outcomes were included. A total of 2109 articles were considered. Conclusions The bibliometric analysis suggests a stable increase in attention towards PND, particularly in general surgery adult-elderly patients, and underlines the importance for the clinicians not to underestimate this specific field.